Nexuses between Governance Quality on Industrial Growth: A Fresh Insight from Developing Economies - Khan, Sarwar; Zafar, Mahwish; Khizar, Sana (iRASD Journal of Economics, 2022)
This study examines the impact of governance on industrial growth. Moreover, this study also examines the impact of trade openness, exchange rate, and inflation on industrial growth in the presence of good and bad governance as well as overall governance. For this purpose, data is extracted from the World Development Indicator (WDI) and World Governance Indicator (WGI) of 47 countries of developing economies from 1984 to 2020. Examining the result Generalized Method of Moments (GMM) technique has been applied. The result shows that an increase in governance significantly improves industrial growth. However, trade openness has a significant relation with industrial growth in well governed countries however it deteriorates in bad governed countries. Whereas improvement in trade will deteriorate the industrial growth in the overall and as well as badly governed countries. In the bad governed countries devaluation of exchange rate significantly deteriorates industrial growth in the long run. On the other hand, Inflation significantly improves industrial growth in good as well as badly governed countries. The government needs to improve governance quality, and exchange rate while badly governed countries need to impose high import duties, produce local products to meet the country’s needs and provide subsidies to exporting industries.